PENGARUH KOMPOSISI CAMPURAN PELAPIS DAN TEKANAN PADA PELEKATAN PELAPISAN BAM/PANI SEBAGAI MATERIAL ABSORBEN MENGGUNAKAN SPRAY GUN - Herlina Kartika; Agus Wijiyanto; Amnur Akhyan (Politeknik Caltex Riau, 2021)
Radar or Radio Detection Ranging is a system of electromagnetic waves to detect and measure long distances. Stealth technology or technology systems that allow objects to be undetected by radar. One of them is Radar Absorbing Material (RAM), a material that has the ability to absorb electromagnetic waves. RAM consists of magnetic and dielectric materials. Barium M-Hexaferrite is used as a magnetic material while Polyaniline (PANi) is used as a dielectric material. Barium M-Hexaferrite synthesis material based on Cilacap Beach Iron Sand and Polyaniline Synthesis material by presenting DBSA. To engineer the magnetic properties of BaM, Cu doping was applied, with an ionic radius of 0.71 nm. BaM and PANi materials were mixed on the blacksteel plate using the spray gun method. The study showed the composition of a mixture of BaM and PANi coatings with a ratio of 26 gr vs 23.4 gr, 23.4 gr vs 26 gr and 15.6 gr vs 15.6 gr and variations in pressure (6.7,8 bar). The test characteristics used hardness test, roughness test, thickness test, and VNA test. In this test, the optimal absorption value from the VNA test was obtained, namely the composition of BaM PANi 23.4 gr vs 26 gr at a pressure of 8 bar with a reflection loss value of -4.6119 dB at a frequency of 11.22 GHz. Keywords: RAM, BaM, PANi,Doping Cu and Spray Gun.